Hydrodynamics of pumps - Brennen, Christopher E. (Christopher Earls), 1941- (Cambridge : Cambridge University Press, 2011)
Hydrodynamics of Pumps is a reference for pump experts and a textbook for advanced students. It examines the fluid dynamics of liquid turbomachines, particularly pumps, focusing on special problems and design issues associated with the flow of liquid through a rotating machine. There are two characteristics of a liquid that lead to problems and cause a significantly different set of concerns than those in gas turbines. These are the potential for cavitation and the high density of liquids, which enhances the possibility of damaging, unsteady flows and forces. The book begins with an introduction to the subject, including cavitation, unsteady flows and turbomachinery, basic pump design and performance principles. Chapter topics include flow features, cavitation parameters and inception, bubble dynamics, cavitation effects on pump performance, and unsteady flows and vibration in pumps - discussed in the three final chapters. The book is richly illustrated and includes many practical examples.
Machine generated contents note: 1. Introduction; 2. Basic principles; 3. Two-dimensional performance analysis; 4. Other flow features; 5. Cavitation parameters and inception; 6. Bubble dynamics, damage and noise; 7. Cavitation and pump performance; 8. Pump vibration; 9. Unsteady flow in hydraulic systems; 10. Radial and rotodynamic forces.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Pumping machinery -- Fluid dynamics; Hydrodynamics